Administrator Development: A Step Beyond Training - John R. Hoyle (Educational Considerations, 1989)
Busy School administrators have too many "fish to fry" to be subjected to remedial, piecemeal, uncoordinated, though well intended "management training." (New Curriculum and Training Techniques.)